Pembuatan Web Pariwisata Dan Sistem Reservasi Hotel Di Kabupaten Karanganyar - Arraniri, Beta, Umi Fadlilah, S.T, M.Eng (2017)
Karanganyar is a city located on the territorial coverage of Ex-Surakarta precisely located in the eastern of Solo city. Karanganyar has many interesting attractions to visit, even more in this year is many attractions object nature, history, and family entertaintment newly opened.Actually Government Tourism Office of Karanganyar cityhas made media web-based information on tourism in Karanganyar, but the media information was only load content only in English language, apart that in that web only showing hotel information and have no reservation system listed on that page. Therefore, the writer has an idea to create a web of tourism in Karanganyar who in Indonesian language. Also on this web will be include a page to reserve a hotel for tourist who want to stay overnight in some hotel. The method used in the making of the website is data search with literature study and field surveys. The result of the implementation of this Final Project is a website that have a map, information about tourist attractions and hotel reservation in Karanganyar